Fuel Oil Consumption and Carbon Intensity Indicator (CII) Monitoring of Container Ship Using Automatic Identification System (AIS) Data - Rama Simatupang; I Made Ariana; Dhimas Widhi Handani (International Journal of Marine Engineering Innovation and Research, 2026)
The IMO has introduced the Carbon Intensity Indicator (CII) to reduce carbon emissions, and it will be mandatory for ships sailing internationally from 1 January 2023. Implementing CII should be a top priority for reducing greenhouse gas emissions from ships sailing in Indonesia’s territorial waters, the world’s largest maritime country. This study aims to determine the constant in the empirical formula for monitoring fuel consumption and CII implementation using Automatic Identification System (AIS) data from MV. Meratus Padang. The Holtrop method is used to calculate the ship’s basic resistance, and the STAWAVE method is then applied to account for environmental conditions during sailing to obtain more accurate results under actual conditions. The total resistance of the Holtrop and STAWAVE methods can be used to calculate the power supplied to the propeller. Furthermore, the propeller’s power can be used to calculate fuel consumption. The fuel consumption calculation showed differences of 0.41% on the Surabaya-Banjarmasin route and -0.35% on the Banjarmasin-Surabaya route, with a propeller efficiency of 0.5 and an engine degradation of 9.5%, as the average CII is “E”.